2012
DOI: 10.1103/physrevb.86.035451
|View full text |Cite
|
Sign up to set email alerts
|

Pt3Zr(0001): A substrate for growing well-ordered ultrathin zirconia films by oxidation

Abstract: We have studied the surface of pure and oxidized Pt3Zr(0001) by scanning tunneling microscopy (STM), Auger electron microscopy, and density functional theory (DFT). The well-annealed alloy surface shows perfect long-range chemical order. Occasional domain boundaries are probably caused by nonstoichiometry. Pt3Zr exhibits ABAC stacking along [0001]; only the A-terminated surfaces are seen by STM, in agreement with DFT results showing a lower surface energy for the A termination. DFT further predicts a stronger … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
103
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(112 citation statements)
references
References 42 publications
(46 reference statements)
7
103
2
Order By: Relevance
“…Figure 2a shows a zirconia film of ≈ 5 ML thickness deposited on Pt(111) and annealed at 640 • C in UHV directly after sputter deposition, leading to the formation of zirconia islands and an ultrathin zirconia film in between. The ultrathin zirconia film shows a Zr-Zr distance of 0.350 ± 0.003 nm, as also observed for Pt 3 Zr(0001) 26 and Pd 3 Zr(0001). 21 The moiré pattern shown in the inset of Figure 2a 26 The creation of the ultrathin film can be reversed by annealing at 640 • C in 5 × 10 −7 mbar O 2 , see Figure 2b.…”
Section: Zirconia On Pt(111) and Ru(0001)supporting
confidence: 72%
See 2 more Smart Citations
“…Figure 2a shows a zirconia film of ≈ 5 ML thickness deposited on Pt(111) and annealed at 640 • C in UHV directly after sputter deposition, leading to the formation of zirconia islands and an ultrathin zirconia film in between. The ultrathin zirconia film shows a Zr-Zr distance of 0.350 ± 0.003 nm, as also observed for Pt 3 Zr(0001) 26 and Pd 3 Zr(0001). 21 The moiré pattern shown in the inset of Figure 2a 26 The creation of the ultrathin film can be reversed by annealing at 640 • C in 5 × 10 −7 mbar O 2 , see Figure 2b.…”
Section: Zirconia On Pt(111) and Ru(0001)supporting
confidence: 72%
“…The ultrathin zirconia film shows a Zr-Zr distance of 0.350 ± 0.003 nm, as also observed for Pt 3 Zr(0001) 26 and Pd 3 Zr(0001). 21 The moiré pattern shown in the inset of Figure 2a 26 The creation of the ultrathin film can be reversed by annealing at 640 • C in 5 × 10 −7 mbar O 2 , see Figure 2b.…”
Section: Zirconia On Pt(111) and Ru(0001)supporting
confidence: 72%
See 1 more Smart Citation
“…[19][20][21] Recently, the oxidation behavior of Pt 3 Zr (0001) surface was studied by the experiment and rst-principles calculations. 22 They found that the weak localized hybridization between Pt and Zr is benecial to oxidation of Zr metal. Note that the metal addition will accelerate the growth of ZrO 2 lm on the Pt 3 Zr (0001) surface.…”
Section: -14mentioning
confidence: 99%
“…A viable approach for the synthesis of ultrathin oxide films is based on the selective oxidation of suitable bimetallic alloys [18][19][20][21][22]. The prototypical example is an ultrathin alumina film on the NiAl(110) substrate [18,23], which has been widely used as a support in model catalytic studies [1,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%